Yet another robot platform for teaching programming: YarpTp (2018)
This paper introduces an implementation of a robot elaborated with Raspberry Pi that accompanies the mentoring of the programming courses given at Universidad Tecnológica de Bolívar as a pedagogic element. This robotic prototype was designed to support the learning of the students who have shortcomings and gaps in knowledges they acquire in their master classes. It describes how it was carried out, as well as important details that append value to the robot. © 2018 IEEE.